SUN-292 knowledge and attitude towards organ donation among peruvian medical residents - Gomez Lujan Md, M. (2020)
Health care professionals are important and critical link in the organ procurement process and therefore, their knowledge and attitudes are essential factors in the promotion of an environment that has a positive influence on organ donation rates. Objective: To assess the knowledge and attitude towards organ donation among medical residents.